Competitiveness and economic-financial performance in the metallurgical industry companies in Romania - M. D. Ungureanu; G. Dobrotă; G. Bălan (Metalurgija, 2015)
The paper presents the level and evolution of indicators for determining the degree of competitiveness in the metallurgical industry in Romania. For this purpose, were used aggregate data for a sample of 22 of the largest companies in Romania operating in metallurgy, for the period 2004 - 2013. The aim of the paper is to identify the factors that determined the negative trend in terms of economic and financial performance of the companies analyzed.